Principles of Public Speaking for College - Uy, Corazon L.; Valdez, Suzette F. (Mandaluyong City, 2009)
This book aims to develop and enhance the student's ability to listen, to write, and specifically to deliver different kinds of speeches into situations students might face in their personal and professional lives. Generally it emphasizes the significance of public speaking in the devel-opment of a diverse and enlightened society. Likewise, this book will hopefully help increase and open the possibility of enriching the student's fromal training in public speaking.
Keywords: Public Speaking